2013
DOI: 10.1097/jto.0b013e31827740f0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Failure, Toxicity, and Survival after Extrapleural Pneumonectomy and Hemithoracic Intensity-Modulated Radiation Therapy for Malignant Pleural Mesothelioma

Abstract: Introduction We investigated safety, efficacy, and recurrence after postoperative hemithoracic intensity-modulated radiation therapy (IMRT) in patients with malignant pleural mesothelioma (MPM)treated with extrapleural pneumonectomy (EPP) during the past decade at a single institution. Methods In 2001–2011, 136 consecutive patients with MPM underwent EPP with planned adjuvant IMRT. Eighty-six patients (64%) underwent hemithoracic IMRT; the rest were not eligible because of postoperative complications, diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 25 publications
6
72
0
Order By: Relevance
“…Improved local control after hemithoracic radiotherapy has been described earlier [10,15]. In our cohort, 59 patients (56%) received adjuvant radiation and the incidence of local tumour recurrence was reduced significantly but without significant influence on OS, which is in line with results from our multicenter randomized controlled trial (MC RCT) of the SAKK 17/04 protocol [13].…”
Section: Discussionsupporting
confidence: 78%
“…Improved local control after hemithoracic radiotherapy has been described earlier [10,15]. In our cohort, 59 patients (56%) received adjuvant radiation and the incidence of local tumour recurrence was reduced significantly but without significant influence on OS, which is in line with results from our multicenter randomized controlled trial (MC RCT) of the SAKK 17/04 protocol [13].…”
Section: Discussionsupporting
confidence: 78%
“…Additional information on surgical procedures, radiation therapy techniques, and methods of data collection for the matched cohort of patients treated with EPP has been reported elsewhere (4). Treatment toxicity, overall survival (OS), progression-free survival (PFS), time to LRF (tLRF), and time to DM (tDM) in patients treated with PD-IMRT were then compared with the matched cohort of patients treated with EPP-IMRT.…”
Section: Matched Comparisonmentioning
confidence: 99%
“…Extrapleural pneumonectomy (EPP) with en bloc resection of the pleura, lung, ipsilateral diaphragm, and pericardium is a high-risk surgery that provides good local control when combined with adjuvant radiation therapy (2)(3)(4). However, recent studies have shown increased morbidity with similar overall survival for EPP versus lung-sparing techniques, despite local recurrence rates between 60% and 100% with lung-sparing surgery alone (5)(6)(7).…”
Section: Introductionmentioning
confidence: 97%
“…Anderson Cancer Center (MDACC) has one of the largest experiences in the use of IMRT after pneumonectomy (12). A retrospective analysis of 86 patients who underwent IMRT after surgery was reported.…”
Section: Radiation After Eppmentioning
confidence: 99%